2015
DOI: 10.1002/aenm.201401869
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Multivalent (Monovalent, Divalent, Trivalent) Ion Insertion in Open Framework Materials

Abstract: The reversible electrochemical insertion of multivalent ions into materials has promising applications in many fi elds, including batteries, seawater desalination, element purifi cation, and wastewater treatment. However, fi nding materials that allow for the insertion of multivalent ions with fast kinetics and stable cycling has proven diffi cult because of strong electrostatic interactions between the highly charged insertion ions and atoms in the host framework.Here, an open framework nanomaterial, copper h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
197
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(208 citation statements)
references
References 71 publications
(184 reference statements)
10
197
0
1
Order By: Relevance
“…Similar discrepancy has been reported in previous studies on the PBA electrode in aqueous electrolytes. 13,14 However, the reason for the discrepancy is not clear at present, and the detailed interpretation of this phenomenon is beyond the scope of the present work. The parts that we must notice in Figures 2a and 2b are the improved electrochemical performances in the superconcentrated electrolyte.…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…Similar discrepancy has been reported in previous studies on the PBA electrode in aqueous electrolytes. 13,14 However, the reason for the discrepancy is not clear at present, and the detailed interpretation of this phenomenon is beyond the scope of the present work. The parts that we must notice in Figures 2a and 2b are the improved electrochemical performances in the superconcentrated electrolyte.…”
mentioning
confidence: 59%
“…11,12 In such a case, an active material with large channels that allow the passage of hydrated polyvalent cations is necessary. Wang et al 13,14 observed that various polyvalent cations could rapidly diffuse into Prussian Blue analogue (PBA) electrodes, which contain large open interstitial sites (4.6 ¡ in diameter) and ©100ª channels (3.2 ¡ in diameter) in polyvalent cation-based aqueous electrolytes. However, the low charge/discharge capacities and capacity reduction during the initial cycles must be improved.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The capacity gradually increased during the initial cycles in both electrolytes. The reason for this phenomenon is unclear at present and a detailed interpretation is beyond the scope of this work, but it may be related to activation or conditioning effects [20,21,26].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, PBAs are notable potential cathode materials for application in ARZIBs owing to their superior characteristics, such as structural stability, large channels, and ease of synthesis [9,18]. Additionally, these materials have large open sites (4.6 Å in diameter) and <100> channels (3.2 Å in diameter), which enable the rapid diffusion of various hydrated metal ions, including zinc ions [19][20][21]. However, the electrochemical performance of these materials has to be improved, as they exhibit relatively low capacities and capacity reduction during the initial cycles.…”
Section: Introductionmentioning
confidence: 99%